(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article analyzes the approaches of leading national scholars to the definition of the concept of "tax reporting". The author characterizes the necessity of tax reporting, since it characterizes the status of an enterprise’s obligations related to the accrual and payment of taxes and other mandatory payments. Tax reporting is submitted to the tax authorities. The purpose of the article is to deepen theoretical research on the essence of the concept of "tax reporting", to disclose the methodology of its preparation with a view to improving its quality, reliability and objectivity. Summarizing the approaches of scholars to the essence of tax reporting, it is worth noting three approaches. According to the first one, tax reporting is considered as a set of documents containing information on the calculation of tax liabilities; according to the second one, it is considered as a set of actions of the taxpayer on preparation and submission of reports; according to the third one, it is considered as a set of consolidated interrelated indicators characterizing the activities of the enterprise for a certain period. Having studied the essence of the concept of "tax reporting", we propose to supplement Article 14 of the Tax Code of Ukraine with the following definition: tax reporting is reporting containing information on the tax liabilities of an enterprise by type of tax and fees. The Ministry of Finance of Ukraine regulates tax reporting by establishing forms of tax returns, calculations and reports by type of tax and fee. The tax reporting procedure can be divided into 4 stages: Stage 1 - selection of the required form of tax reporting in accordance with the type of tax/fee; Stage 2 - preparation of a tax return for the tax/fee, i.e., entering data directly; Stage 3 - verification of the document for correctness of preparation, compliance of the entered data with the accounting data, correctness of determination of the tax base, taxable object, tax rate; Stage 4 - signing of tax reports. Based on the study of tax reporting on national taxes and fees, it should be noted that not all forms contain information on the procedure for their preparation. For the preparation of individual forms by type of tax and fees, notes are used after the main part of the tax reporting. Therefore, we believe that the central executive body that ensures the formation and implementation of the state financial policy should develop recommendations on the preparation of tax reporting forms for those taxes and fees that do not have them, as this will contribute to better coverage of information on tax liabilities and significantly reduce the number of pages of tax reports.